(untitled) - Overman, Larry E. (New York, 2006)
Organic Reactions is a comprehensive series of volumes composed of chapters devoted to important synthetic reactions. For each volume, the chapter authors are world-renowned experts with extensive hands-on experience in the field. The chemistry is presented from a preparative point of view and particular attention is given to reaction limitations, interfering influences, effects of chemical structure, and the selection of experimental conditions.
Keywords: Chemistry, organic,Chemical reactions,Hóa hữu cơ,Phản ứng hóa học